Private dwelling : contemplating the use of housing - King, Peter, 1960-2023 (Routledge, 2004)
This book considers the personal and subjective use of housing and the ways we use our housing, as well as discussion of a method for analysing these actions.
Keywords: Housing.; Housing -- Psychological aspects.; Functionalism (Social sciences); Fonctionnalisme (Sciences sociales); SOCIAL SCIENCE -- General.; BUSINESS & ECONOMICS -- Infrastructure.; Housing; Housing -- Psychological aspects